Réponses

  • Utilisateur Brainly
2014-04-12T09:15:29+02:00
On considère l'expression suivante: D=(5x-2)²+(5x-2)(2x+7)
1.Développer et réduire D
D=25x²-20x+4+10x²-4x+35x-14
  =35x²+11x-10

2.Factoriser D

D=(5x-2)(5x-2+2x+7)
  =(5x-2)(7x+5)
2014-04-12T10:31:13+02:00
Salut :)

D = (5x - 2)² + (5x - 2)(2x + 7)

1. Développer et réduire D :
D = (5x - 2)² + (5x - 2)(2x + 7)
D = (5x)² - 2 x 5x x 2 + 2² + 5x x 2x + 5x x 7 - 2 x 2x - 2 x 7
D = 25x² - 20x + 4 + 10x² + 35x - 4x - 14
D = 35x² + 11x - 14

2. Factoriser D
:
D = (5x - 2)² + (5x - 2)(2x + 7)
D = (5x - 2)(5x - 2) + (5x - 2)(2x + 7)
D = (5x - 2)[(5x - 2) + (2x + 7)]
D = (5x - 2)(5x - 2 + 2x + 7)
D = (5x - 2)(7x + 5)

J'espère t'avoir aidé(e) ! :)